Space division approach to implement a shared buffer in an ATM switch. - Pao, Derek C.W (Computer communications.)
In this paper, we propose a space division approach to implement a shared buffer in an ATM switch which does not require scaling up the bandwidth of the shared memory. At the normal operating point, cell losses are infrequent and overloading of individual output ports is likely to occur at different time instances. An external 'shared' buffer can be time-multiplexed to serve the overloaded output ports on demand. To achieve this, the switch provides an additional feedback path for derouting cells destined for an overloaded output port to the shared buffer. When the traffic load at the corresponding output port drops and buffer space becomes an available in the output queue, the derouted cells will be removed from the shared buffer and routed via the switching fabric to their destinations. Simulation results reveal that by incorporating a shared buffer of size 128, the acceptable load of the switch can be substantially increased, especially for bursty traffic conditions.